Children’s Language Development from the Perspective of the Al-Qur’an - Supandi Supandi; Samaher Samaher (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2025)
This article explores children’s language development from the perspective of the Al-Qur’an and contemporary developmental theory. Language is viewed in Islam as a divine gift that shapes thought, identity, and moral behavior. The Qur’an emphasizes that Allah teaches humans the ability to speak (Qur’an 55:1–4), indicating that language development is both natural and God-guided. Drawing on psychological and educational literature, this study highlights that children acquire language through interaction, imitation, and meaningful communication within their social context, particularly the family. Qur’anic narratives, such as the dialogue between Luqman and his son, illustrate the importance of nurturing speech through wisdom, affection, and moral guidance. The discussion reveals that language development in Islamic thought is holistic, integrating emotional, intellectual, social, and spiritual dimensions. Early exposure to positive communication, Qur’anic recitation, and ethical language use supports both linguistic competence and faith development. The article concludes that parents and educators play a central role in shaping language environments that are dialogic, value-oriented, and spiritually enriching. This integrated approach offers an alternative conceptual framework for understanding language development that connects scientific insight with religious wisdom, particularly within Muslim educational contexts.